2005
DOI: 10.1002/rcm.1835
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of isomeric allylic diols resulting from chlorophyll phytyl side‐chain photo‐ and autoxidation by electron ionization gas chromatography/mass spectrometry

Abstract: The electron ionization (EI) mass spectral fragmentation of the trimethylsilyl derivatives of 3-methylidene-7,11,15-trimethylhexadecane-1,2-diol, Z- and E-3,7,11,15-tetramethylhexadec-3-ene-1,2-diols and Z- and E-3,7,11,15-tetramethylhexadec-2-ene-1,4-diols resulting from chlorophyll phytyl side-chain photo- and autoxidation was investigated. Different pathways (substantiated by deuterium labelling) were proposed in order to explain the main fragmentation observed. Then, some sufficiently specific fragment ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…In plants, phytol is derived from the first step of chlorophyll degradation, which is catalyzed by chlorophyllase (EC 3.1.1.14) (Tsuchiya et al, 1999); however, the latter enzymatic steps of phytol degradation are poorly understood, especially in comparison with the pathway in humans. Previous studies have suggested that phytol degradation during leaf senescence occurs via photooxidative conversion into various isoterpenoid compounds (Rontani et al, 1996;Matile et al, 1999;Rontani and Aubert, 2005). This obviously cannot be the case for chlorophyll breakdown during the extended dark treatments in this study.…”
Section: The Involvement Of Etfqo In the Phytol Catabolic Pathway In mentioning
confidence: 53%
“…In plants, phytol is derived from the first step of chlorophyll degradation, which is catalyzed by chlorophyllase (EC 3.1.1.14) (Tsuchiya et al, 1999); however, the latter enzymatic steps of phytol degradation are poorly understood, especially in comparison with the pathway in humans. Previous studies have suggested that phytol degradation during leaf senescence occurs via photooxidative conversion into various isoterpenoid compounds (Rontani et al, 1996;Matile et al, 1999;Rontani and Aubert, 2005). This obviously cannot be the case for chlorophyll breakdown during the extended dark treatments in this study.…”
Section: The Involvement Of Etfqo In the Phytol Catabolic Pathway In mentioning
confidence: 53%
“…Quantification was thus carried out with standards of two highly structurally related compounds. Diol 2 was quantified using an external standard of 3,7,11,15‐tetramethylhexadecan‐1,2‐diol ( 4 ) produced by Pd/CaCO 3 ‐catalyzed hydrogenation of 3‐methylidene‐7,11,15‐trimethylhexadecan‐1,2‐diol ( 5 ) whose synthesis was described previously, while quantification of acid 3 was carried out with 2,6,10,14‐tetramethylpentadecanoic acid (pristanic acid) ( 6 ) (Sigma Aldrich, St. Quentin Fallavier, France).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the very low amounts of IP 25 available, compounds 2 and 3 could not be produced in sufficient amounts to permit quantification, although comparison of their mass fragmentations and retention times with those of compounds detected in sediments allowed their hydrogenation of 3-methylidene-7,11,15-trimethylhexadecan-1,2-diol (5) whose synthesis was described previously, 12 while quantification of acid 3 was carried out with 2,6,10,14-tetramethylpentadecanoic acid (pristanic acid) (6) (Sigma Aldrich, St. Quentin Fallavier, France).…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 3-methylidene-7,11,15-trimethylhexadecan-1,2-diol (phytyldiol), 3,7,11,15-tetramethylhexadec-3(Z/E)-en-1,2-diols and 3,7,11,15-tetramethylhexadec-2en-1,4-diols was described previously [28]. 24-Methylcholesta-5,22-dien-3b-ol and 24-methylcholesta-5,24 (28)-dien-3b-ol were purchased from Sigma-Aldrich.…”
Section: Preparation Of Oxidation Standardsmentioning
confidence: 99%